Reconstruction of pressure ulcers with flaps in a tertiary care centre - Gopalakrishnan, Ravikumar; Rajalingam, Manoharan; Rajagunasekaran, Balamuralee; Esakimuthu, Ramya (International Surgery Journal, 2021)
Background: Patients with pressure ulcers have multiple risk factors and develop various post- operative complications. The purpose of the study is to analyse the outcome of management of pressure ulcers with different flaps. Methods: This is a retrospective study done in a series of patients who underwent flap reconstruction of pressure ulcers between 2016 and 2019 in the Department of Plastic and Reconstructive Surgery, Thanjavur medical college, Tamilnadu, India. Totally twenty-eight patients were operated for stage III and stage IV pressure ulcers with various types of flaps depending upon the site of pressure ulcers. Post operatively flaps were monitored for viability and post-operative complications. Results: Total 22 males, 5 females and 1 male child had undergone surgery for pressure ulcers. The age group ranged from 3years to 62 years with an average of 37 years. The sites of the pressure ulcers were as follows: 14 (50%) sacral; 10 (35.7%) ischial; 3 (10.7%) trochanteric and 1 (3.6%) multiple pressure ulcers. Most of the patients (60.7%) had traumatic paraplegia and developed pressure ulcers. 18 patients with stage III and 10 patients with stage IV pressure sores were operated with different flaps. Duration of treatment ranged from 29 to 118 days. The mean hospitalization was 78 days. Conclusions: Effort is needed to prevent the development of pressure ulcers through the early identification of risk and early implementation of preventive measures. Flap cover is ideal to prevent recurrence. Post-operative follow- up with physiotherapy and rehabilitation are very important.